2015
DOI: 10.1103/physreve.91.043001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the flow in a soft tube deformed due to an applied pressure gradient

Abstract: A linear stability analysis is carried out for the flow through a tube with a soft wall in order to resolve the discrepancy of a factor of 10 for the transition Reynolds number between theoretical predictions in a cylindrical tube and the experiments of Verma and Kumaran [J. Fluid Mech. 705, 322 (2012)]. Here the effect of tube deformation (due to the applied pressure difference) on the mean velocity profile and pressure gradient is incorporated in the stability analysis. The tube geometry and dimensions are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Thus, a multi-fold reduction in the transition Reynolds number has been demonstrated for the flow conduits with compliant walls. The transition at high Reynolds number seems to be captured by an approximate local stability analysis of Verma & Kumaran (2013, 2015) (§ 8.2.2), in contrast to the flow in rigid tubes/channels where the linear stability analysis does not accurately predict transition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, a multi-fold reduction in the transition Reynolds number has been demonstrated for the flow conduits with compliant walls. The transition at high Reynolds number seems to be captured by an approximate local stability analysis of Verma & Kumaran (2013, 2015) (§ 8.2.2), in contrast to the flow in rigid tubes/channels where the linear stability analysis does not accurately predict transition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a stability analysis which considers a steady and fully developed base state may not accurately predict the experimental results. Stability analyses which incorporate the deformation due to the pressure gradient have been carried out (Verma & Kumaran 2012, 2015), as indicated in § 8.2.2. Here, the deformed shape is determined from experimental measurements, and the stability analysis is carried out at different downstream locations assuming the flow is unidirectional.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The change in the scaling was explained on the basis of the flow modification due to the tube convergence, and the consequent increase in the strain rate at the wall. A more detailed calculation (Verma & Kumaran 2015) indicated that the quantitative decrease in the Reynolds number is due to the modification in the velocity and pressure profiles caused by the deformation of the wall of the tube. The detailed shape of the tube wall was measured in the experiments.…”
Section: High Reynolds Numbermentioning
confidence: 98%